The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10570-014-0524-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility and immunomodulatory properties of wood based nanofibrillated cellulose

Abstract: Cellulose nanofibrils (CNFs), unique and promising natural materials have gained significant attention recently for biomedical applications, due to their special biomechanical characteristics, surface chemistry, good biocompatibility and low toxicity. However, their long bio-persistence in the organism may provoke immune reactions and this aspect of CNFs has not been studied to date. Therefore, the aim of this work was to examine and compare the cytocompatibility and immunomodulatory properties of CNFs in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 49 publications
(69 reference statements)
6
51
0
1
Order By: Relevance
“…CNFs were added to mo-DC cultures during the differentiation phase, in two different concentrations of CNFs (100 and 500 μg/ml) that were not cytotoxic in our previous study29.…”
Section: Resultsmentioning
confidence: 97%
“…CNFs were added to mo-DC cultures during the differentiation phase, in two different concentrations of CNFs (100 and 500 μg/ml) that were not cytotoxic in our previous study29.…”
Section: Resultsmentioning
confidence: 97%
“…However, in both studies extremely high nanocellulose concentrations in respect to mammalian cell culture (0.25–5 mg/mL) were used [8688]. Of note in this regard is the study by Colic and co-authors [89], who showed that only the exposure to extremely high concentrations of long, entangled cellulose nanofibrils (33 ± 2.5 µm × 10–10 nm; 0.25–1 mg/mL), the highest one covering the L929 monolayers almost completely, lead to impaired metabolic activity and reduced cell proliferation [89]. Furthermore in vivo, Yanamala measured elevated cytotoxicity (as determined by an increase in the activity of the enzyme lactate dehydrogenase) after the aspiration of wood pulp derived CNCs in mice (50, 100 and 200 μg/mouse), detecting similar strong reactions in the context of cytotoxicity compared to asbestos aspiration (50 μg/mouse) [90].…”
Section: Introductionmentioning
confidence: 99%
“…These results are underpinned by a study of Catalan et al, who exposed monocyte derived macrophage monocultures to 30–300 µg/mL cotton CNCs (135 ± 5 × 7.3 ± 0.2 nm) with no detection of TNF-α and IL-1β in comparison to microcrystalline cellulose (CNC aggregates that were micron-sized) [92]. Interestingly, Colic and co-workers showed an anti-inflammatory influence of cellulose nanofibril exposures on PBMCs (peripheral blood mononuclear cells) in vitro, as measured by downregulation of IL-2, IFN-γ (interferon-γ) and IL-17, of, which was only observed at considered high doses (0.25–1 mg/mL) [89]. However, Clift et al (220 ± 6.7 × 15 ± 5 nm) [91], who used the same 3D triple-cell co-culture model of the human epithelial tissue barrier highlighted above and applied CNCs via aqueous suspensions, showed an increase in IL-8 response when exposed to 30 µg/mL cotton CNCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a wide application spectrum is related mainly to their nanometer-sized features, large surface area, specific biomechanical characteristics, surface chemistry, ease of conjugation, high biocompatibility, and low (if any) cytotoxicity (Alexandrescu et al 2013) with tolerogenic potential to the immune system (Tomić et al 2016). Due to a general acceptance as˝biosafe˝nanomaterial (Č olić et al 2014;Tomić et al 2016), the cellulose nanocrystals (CNCs), with typical sizes of \300 nm in length and around 10 nm in diameter (Habibi et al 2010), have also been readily evaluated as catalysis (Zhou et al 2013) in biomedical engineering (Sinha et al 2015), as well as targeted drugs (Taheri & Mohammadi 2015) and gene (Hu et al 2015) delivery. Recent studies also demonstrated the potential of CNCs to target tumours via the Enhanced Permeability and Retention (EPR) effect and delivery of organic compounds or drugs into cancer cells (Drogat et al 2011).…”
Section: Introductionmentioning
confidence: 99%